2007
DOI: 10.1002/da.20234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics in episodic and chronic obsessive–compulsive disorder

Abstract: Our objective in this study was to compare the demographics and clinical characteristics of patients with episodic and chronic obsessive-compulsive disorder (OCD). We recruited 128 outpatients with a primary diagnosis of OCD according to DSM-IV diagnostic criteria. The episodic (n=24) and chronic (n=104) OCD patient groups were compared with respect to demographic variables and scores from various psychiatric rating scales. The severity of compulsions was found to be significantly lower in the episodic OCD gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
2
21
0
1
Order By: Relevance
“…Some outcome studies have found that severity was not predictive of long-term outcome. 2,4 Our finding that severity is significantly associated with a lower likelihood of remission is consistent with a number of studies, 17,19 including a recent study that, like our study, was naturalistic and used multiple time points to assess course. 21 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Some outcome studies have found that severity was not predictive of long-term outcome. 2,4 Our finding that severity is significantly associated with a lower likelihood of remission is consistent with a number of studies, 17,19 including a recent study that, like our study, was naturalistic and used multiple time points to assess course. 21 …”
Section: Discussionsupporting
confidence: 90%
“…4,1419 Four prospective studies in particular have reported on the long-term course of treatment-seeking adults with OCD in naturalistic clinical settings. 1416,18 Rates of achieving at least partial remission (subclinical OCD symptoms) range from 52% of 66 outpatients treated over a 2-year prospective period in a US OCD specialty clinic 15 to 76% of 75 patients followed up 11–13 years after initial treatment at a psychiatric hospital in India.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the bipolar spectrum concept in the general population (48), a study reported 53.3% and 30% of BD-OCD and BD-II-OCD patients respectively (15). In hospital-based studies, the lifetime prevalence of comorbid BD in OCD adult patients ranged between 7% and 55.8% (17,(49)(50)(51)(52)(53)(54)(55)(56)(57). When restricting the analysis to studies with sample size greater than 250, the BD-OCD prevalence range was narrower (11-15.7%) (17,51,53), and the mean prevalence rate of BD-I comorbidity was 3.7%, while BD-II was 9.5% (17,51,53,58).…”
Section: Included Studiesmentioning
confidence: 99%
“…They suggested the stable traits may relate more to genetics and biology and constitute prime targets for biological treatments, whereas the latter may relate more to nurture and learning and represent targets for psychosocial interventions. 43 Similarities have been noted between the course of OCPD and OCD, with onset relatively early in life 77 and a chronic, fluctuating course 78,79 (although a subsample of OCD with episodic illness has also been described). A retrospective, long-term study directly comparing first psychiatric admissions diagnosed with OCD or OCPD showed similar levels of diagnostic stability over up to 8 years of follow-up.…”
Section: Coursementioning
confidence: 94%